Insight into the integration effect of chitosan and β-cyclodextrin on the properties of zinc-phosphate/hydroxyapatite hybrid as delivery structures for 5-fluorouracil: loading and release profiles - Bin Jumah, May N.; Al Othman, Sarah I.; Alomari, Awatif Abdulaziz; Allam, Ahmed A.; Bellucci, Stefano; Abukhadra, Mostafa R. (Frontiers in Chemistry, 2024)
Zinc-phosphate/hydroxyapatite hybrid form (ZP/HP) in core-shell nanostructure was developed and functionalized with both chitosan (CS@ZP/HP) and β-cyclodextrin (CD@ZP/HP) as bio-composite of enhanced physicochemical and biological properties. These structures were assessed as potential deliveries of 5fluorouracil, exhibiting enhanced loading, release, and anti-cancer behaviors. The functionalization strongly prompted the loading effectiveness to be 301.3 mg/g (CS@ZP/HP) and 342.8 mg/g (CD@ZP/HP) instead of 238.9 mg/g for ZP/HP. The loading activities were assessed based on the hypotheses of traditional kinetic and isotherm models, alongside the computational variables of the monolayer model with a single energetic site as an advanced isotherm model. The functionalized versions exhibit much greater loading efficacy compared to ZP/HP as a result of the increment in the density of the existing loading sites (Nm (5-Fu) = 78.85 mg/g (ZP/HP), 93.87 mg/g (CS@ZP/HP), and 117.8 mg/g (CD@ZP/HP)). Furthermore, the loading energies of approximately 40 kJ/mol, together with the loading potential of each receptor (n > 1) and Gaussian energies of approximately 8 kJ/mol, indicate the physical entrapment of 5-Fu molecules according to a vertical orientation. The materials mentioned verify long-term and continuous release characteristics. Following the modification processes, this behavior became faster as both CS@ZP/HP and CD@ZP/HP displayed complete release within 120 hours at pH 1.2. The kinetic studies and diffusing exponent (> 0.45) indicate that release characteristics are controlled by both diffusion and erosion processes. These carriers also markedly increase the cytotoxicity of 5-Fu against HCT-116 colorectal cancer cell lines: 5-Fu-ZP/HP (3.2% cell viability), 5-Fu-CS@ZP/HP (1.12% cell viability), and 5-Fu-CD@ZP/HP (0.63% cell viability).